Preliminary assessment of waste heat recovery solution to enhance the performance of Liquid Air Energy Storage system - Tafone, Alessio (2017)
This work investigates the thermodynamic feasibility of an integrated energy system consisting of a Liquid Air Energy Storage system and Organic Rankine Cycle (ORC) in order to fully recover the waste heat discharged by the charge phase. Different integrated LAES-ORC system configurations have been modelled by means of the numerical software EES-Engineering Equation Solver v.10, which allows to compute the thermo-physical properties of the working fluids throughout the whole cycles. The LAES-ORC integrated systems are compared in terms of different performance indices such electric power output, round trip efficiency of stand-alone and integrated systems and recover efficiency of ORC. In addition, the economic feasibility of the integrated system has been assessed to evaluate the impact of ORC introduction in LAES economy. The results show that a tight integration between LAES and ORC allows to significantly improve the round efficiency (up to 20%) and reduce the pay-back period of stand-alone LAES as high as 6 %.